Open Source for Global Public Goods - World Bank (World Bank, Washington, DC, 2020)
This technical note is intended to contribute to understanding of how to leverage open source software (OSS) for global public goods particularly in resource-constrained environments. The aim is to enable a more deliberate approach to building information systems that can serve as a global public good, rather than reinventing the wheel every time. Despite business processes being largely the same in various country contexts, each new project is typically built from scratch, as if there were no templates, code libraries or models, or lessons learned on which to base new implementations. Implementations in some domains are dominated by a few IT vendors that present significant switching costs and lock-in to governments that are already resource constrained. OSS solutions have the potential to address the challenges mentioned above and facilitate efficiency, robustness, security, and interoperability of information systems. Governments in the digital age are interested to learn how OSS solutions can help build open, robust, interoperable, and secure service delivery platforms. Digital technology is increasingly the way citizens interact with government. From submitting passport applications to paying parking tickets and registering for social assistance, prior in-person interactions are now occurring online. For governments, modern identification (ID) systems allow for more efficient and transparent administration and service delivery, a reduction in fraud and leakage related to transfers and benefits payments, increased security, accurate vital statistics for planning purposes, and greater capacity to respond to disasters and epidemics. Equally important, social protection systems, programs, and policies help buffer individuals from shocks and equip them to improve their livelihoods and create opportunities to build a better life for themselves and their families.